Reproductive politics and women's empowerment; how does geopolitics control women? - Delanerolle, Gayathri; Elneil, Sohier; Sivakumar, Abirame; Kurmi, Om; Pathiraja, Vindya; Ikwuka, David; Nguyen, Nhan Thi; Rathnayake, Nirmala; Phiri, Peter; Eleje, George Uchenna (Frontiers in Global Women's Health, 2025)
Reproductive politics lie at the intersection of gender, power, and governance, shaping women's autonomy through laws, policies, and cultural norms. Historically, colonialism and population control initiatives marginalized women, particularly in the Global South, fostering distrust in healthcare systems. Feminist movements advocate for reproductive justice, yet economic and nationalistic interests continue to influence access to care. Governments regulate reproduction to control demographics, labor markets, and national power. Pronatalist and antinatalist policies, such as China's One-Child Policy, have led to coercive interventions, disproportionately affecting marginalized communities. Reproductive politics also shape masculinity, fatherhood, and state-controlled family structures. Global reproductive policies reflect ideological struggles, from restrictive abortion laws in Poland and the U.S. to progressive approaches in Nepal and Vietnam. Socioeconomic barriers further limit access to contraception, maternal healthcare, and fertility treatments. Achieving reproductive justice requires inclusive policies, healthcare reform, and recognition of reproductive rights as fundamental to gender equality.